2022
DOI: 10.3389/fgene.2022.994741
|View full text |Cite
|
Sign up to set email alerts
|

FDX1 expression predicts favourable prognosis in clear cell renal cell carcinoma identified by bioinformatics and tissue microarray analysis

Abstract: Ferredoxin 1 (FDX1), an iron-sulphur protein, is responsible for electron transfer in a range of metabolic redox reactions. Clear cell renal cell carcinoma (ccRCC) is an aggressive cancer characterised by metabolic reprogramming, and FDX1 is a critical regulator of cuproptosis. However, the expression profile and prognostic value of FDX1 associated with clinicopathological features in ccRCC remain largely unelucidated. In this study, we integrated a series of public bioinformatic analysis to explore the mRNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…Our research also showed that FDX1 methylation could be observed during transcription, and the transcribed protein was expressed in normal tissues but not in tumors. This finding is supported by those of other studies [ 12 , 19 , 20 ]. Moreover, high FDX1 expression was associated with better OS according to TCGA and Array Express databases ( P < 0.05).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our research also showed that FDX1 methylation could be observed during transcription, and the transcribed protein was expressed in normal tissues but not in tumors. This finding is supported by those of other studies [ 12 , 19 , 20 ]. Moreover, high FDX1 expression was associated with better OS according to TCGA and Array Express databases ( P < 0.05).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we used an external database and qRT-PCR experiments for validation. The experimental results obtained by Zhang and Huang are consistent with our results [ 12 , 19 ]. Our research also showed that FDX1 methylation could be observed during transcription, and the transcribed protein was expressed in normal tissues but not in tumors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The Cuproposis score was strongly correlated with the infiltration levels of various immune cells in the TME [ 113 , 114 ]. As a critical regulator of cuproptosis, FDX1 sparked greater interest in favorable prognosis in ccRCC than other individual prognostic parameters [ 115 , 116 ]. Similarly, cuproptosis-related lncRNA also show pretty predicting potential [ 117 ].…”
Section: Cuproptosismentioning
confidence: 99%
“…Because DLAT and DLST are components of the TCA cycle, FDX1 then directs oligomerization of DLAT and DLST, reducing their levels; this implies that cuproptosis targets components of the TCA cycle ( Tsvetkov et al, 2022 ). It has been demonstrated that mitochondrial respiration is associated with copper death; excess copper promotes aggregation of lipoylated protein and reduces iron-sulfur cluster protein; this triggers aggregation and dysregulation of these proteins, blocking the TCA cycle, leading to proteotoxic stress and ultimately cell death ( Huang et al, 2022 ). Briefly, cuproptosis mainly depends on intracellular copper accumulation and the TCA cycle, while FDX1 and proteolipidation are key regulators ( Figure 4 ).…”
Section: Overview Of Mechanical Network In Novel Programmed Cell Deathmentioning
confidence: 99%